2022
DOI: 10.1038/s41598-022-22309-7
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blinded, placebo-controlled, crossover study of the HCN channel blocker ivabradine in a capsaicin-induced pain model in healthy volunteers

Abstract: Hyperpolarization-activated cyclic nucleotide-gated (HCN) channels have been focused on as a potential therapeutic target for inflammatory and neuropathic pain in rodent models. However, roles of HCN channels in human pain states have been scarcely investigated. We evaluated analgesic effects of 2-day administration of ivabradine, the only clinically available HCN channel blocker, on a capsaicin pain model in a randomized, double-blinded, placebo-controlled, crossover study. Twenty healthy adult subjects (18 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…23,24 Highly expressed in the nervous system, HCN channels govern action potential genesis thresholds in nociceptive neurons and contribute to rhythmic/spontaneous firing patterns underlying pain signaling. 25,26 Dexmedetomidine may dampen neuronal excitability by inhibiting HCN currents, raising firing thresholds and decreasing responsiveness to painful stimuli. This attenuates the propagation of pain signals along sensory neurons, enhancing lidocaine anesthesia and analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Highly expressed in the nervous system, HCN channels govern action potential genesis thresholds in nociceptive neurons and contribute to rhythmic/spontaneous firing patterns underlying pain signaling. 25,26 Dexmedetomidine may dampen neuronal excitability by inhibiting HCN currents, raising firing thresholds and decreasing responsiveness to painful stimuli. This attenuates the propagation of pain signals along sensory neurons, enhancing lidocaine anesthesia and analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, human clinical trials of the I h blocker ivabradine failed to demonstrate analgesic effects in capsaicin pain models (Lee et al., 2019; Tanaka et al., 2022). Additionally, clinical trials of ivabradine in patients with chronic peripheral neuropathic pain showed no significant treatment effect on the primary endpoint.…”
Section: Introductionmentioning
confidence: 99%